Evidence on manganese peroxidase and tyrosinase expression during decolourization of textile industry dyes by Trichosporon akiyoshidainum - Pajot, Hipólito Fernando (2011)
Textile dyes are engineered to be resistant to environmental conditions. During recent years the treatment of textile dye effluents has been the focus of significant research because of the potentially low cost of the process. Mechanisms of biological textile dye decolorization depend greatly on the chemical structure of the dye and the microorganisms used. While basidiomycetous filamentous fungi are well recognized for dye decolorization through ligninolytic enzymes, reports on textile dye decolorization mechanisms of basidiomycetous yeasts have been scarce. Decolorization of several textile dyes by Trichosporon akiyoshidainum occurs during the first 12 h of cultivation. This fast decolorization process could not be solely related to siderophore production or dye sorption to biomass; it was shown to be a co-metabolic process. T. akiyoshidainum could use glucose, sucrose, and maltose as alternative carbon sources, and urea as an alternative nitrogen source with similar decolorization rates. The activity of two enzymes, manganese peroxidase and tyrosinase, were induced by the presence of dyes in the culture media, pointing to their potential role during the decolorization process. Manganese peroxidase titers reached 666 U l 1 to 10538 U l 1, while tyrosinase titers ranged between 84 U l 1 and 786 U l 1, depending on the dye tested. The present work provides a useful background to propose new ecofriendly alternatives for wastewater treatment in textile dying industries.